FATE AND FREEWILL - Rao, Subba (International Journal of Research -GRANTHAALAYAH, 2020)
The raison d’etre of human birth is liberation from bondage. Man appears to be practically a slave to the efforts of his past karma, but he is a free agent with regard to fresh and independent deeds. If these fresh and independent deeds resulting from his free will are in any manner directed to thwart the effects of his past karma, he seems to be doomed to failure. The acuteness of his failure seems to be proportionate to the disparity between the forces of fate and resisting will-power. On the other hand, if the fresh and the independent deeds are directed into neutral fields and neutral periods, the success appears to be proportionate to the force of the will and the effort put forward. It is through this free will, with which man responds to fate by deed and thought, that he stores up the good or bad karma for the life to come, in other words, elevates himself to obtain liberation from death or brings himself down from life to life encircling in the endless death-birth cycle. Today’s freewill is tomorrow’s destiny. While action is always present, the occurrence of reaction depends on the individual’s motive and the action itself. It is this view of a harmonious combination of fate and free will that seems to account for the baffling inequities in life, while affording an answer to the perennial subject of Fate Versus Free Will.